2021
DOI: 10.1096/fj.202001646rr
|View full text |Cite
|
Sign up to set email alerts
|

Reduced RECK levels accelerate skeletal muscle differentiation, improve muscle regeneration, and decrease fibrosis

Abstract: The muscle regeneration process requires a properly assembled extracellular matrix (ECM). Its homeostasis depends on the activity of different matrix-metalloproteinases (MMPs). The reversion-inducing-cysteine-rich protein with kazal motifs (RECK) is a membrane-anchored protein that negatively regulates the activity of different MMPs. However, the role of RECK in the process of skeletal muscle differentiation, regeneration, and fibrosis has not been elucidated. Here, we show that during skeletal muscle differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 112 publications
(284 reference statements)
0
5
0
Order By: Relevance
“…In hepatocellular carcinoma, RECK expression is associated with less vascular invasion, as well as immunogenic features such as recruitment of tumor-infiltrating lymphocytes and expression of immune checkpoint molecules, including programmed cell death ligand 1 (PD-L1) [64]. In the muscle regeneration process, it has been reported that notch-1 signaling is reduced, while p38 and AKT signaling are augmented in myoblasts with decreased RECK expression levels [65]. Our understanding of the RECK molecular regulation mechanism mediating miR-21 microRNA function in cancer generally and the cervical carcinogenesis process specifically remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, RECK expression is associated with less vascular invasion, as well as immunogenic features such as recruitment of tumor-infiltrating lymphocytes and expression of immune checkpoint molecules, including programmed cell death ligand 1 (PD-L1) [64]. In the muscle regeneration process, it has been reported that notch-1 signaling is reduced, while p38 and AKT signaling are augmented in myoblasts with decreased RECK expression levels [65]. Our understanding of the RECK molecular regulation mechanism mediating miR-21 microRNA function in cancer generally and the cervical carcinogenesis process specifically remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, RECK expression is associated with less vascular invasion, as well as PD-L1 expression [68]. In the muscle regeneration process, it has been reported that notch-1 signaling is reduced, while p38 and AKT signaling are augmented in myoblasts with decreased RECK expression levels [69]. Our understanding of the RECK molecular regulation mechanism mediating miR-21 microRNA function in cancer generally and the cervical carcinogenesis process specifically remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Reversion-inducing-cysteine-rich protein with kazal motifs (RECK) is a membrane-anchored protein that negatively regulates the activity of different MMPs. RECK’s role in skeletal muscle differentiation, regeneration, and fibrosis have only recently been explored, but one study showed that, during myogenic differentiation of C2C12 myoblasts and satellite cells on isolated muscle fibers, RECK was transiently upregulated, and upregulation alternated with periods of RECK reduction [ 42 ]. Additionally, when RECK levels were reduced, C2C12 myoblasts were likely to enter their differentiation program with an accelerated differentiation process.…”
Section: Survey Of Engineered Cell–ecm–materials Interactions In Musc...mentioning
confidence: 99%
“…In vivo results indicated that the transient upregulation of RECK occurs during skeletal muscle regeneration and is accelerated in RECK± mice. The RECK± mice had diminished fibrosis in response to chronic muscle damage compared to WT controls, suggesting that RECK acts as a myogenic repressor during muscle formation and regeneration [ 42 ]. Attenuating the effects of RECK in the ECM may prove useful for engineered and regenerative muscle therapies.…”
Section: Survey Of Engineered Cell–ecm–materials Interactions In Musc...mentioning
confidence: 99%